The Coexistence of Croats and Serbs in the Pre-War and Post-War Period – An Implicite Critique of the War in Croatia as an Ethnic Conflict - Dragutin Babić (Migracijske i etničke teme, 2004)
The paper analyses the forms of coexistence between Croats and Serbs in the pre-war, war and post-war periods. The struggle for recognizing the right to self-determination of the republics of former Yugoslavia as well as denials of this right, which led to the attack by the Yugoslav army on Slovenia and Croatia, mainly destroyed the net of primary social relations in local communities affected by the war. However, even in war conditions, some segments of the neighbourhood and friendship networks remained intact on the local level. Some Croats and Serbs protected one another during the war. Pre-war coexistence and developed forms of social interaction and communication between Croats and Serbs as well as the preserved segments of micro-social ethnic networks during the war and the revival of coexistence between Croats and Serbs in the post-war period, indicate the strength and resistance of primary structures in local communities. This puts in doubt the interpretation of the war in Croatia as an ethnic conflict, and affirms the thesis that it was above all a political-state conflict. Events in former war areas in Croatia (in official terminology: areas of special state concern), together with the gradual, slow but nevertheless upward trend in the revival of coexistence, reveals the reasons/motives of the conflict. The conflicts were not the result of age-old hatreds, intolerance and long-standing local conflicts, but rather the consequence of opposed political projects advocated by the representatives of Croats and Serbs in Croatia. This is also the main argument for defining the political/military conflict in Croatia as above all a political/state conflict and not an ethnic one.